Between Knowing and Acting: Peran Literasi Kesehatan Mental dan Pencarian Bantuan terhadap Self-Harm pada Mahasiswa - Fitriana, Qurrota A'yuni Fitriana (Syntax Corporation, 2024)
Self-harm is a serious mental health issue among university students. Understanding the factors that contribute to this behavior needs to be a focus for a number of parties. This study aimed to identify the role of mental health literacy and help-seeking as factors influencing self-harm behaviour among university students. Data were collected through online psychological scales from a sample of 323 university students. Data analysis used multiple linear regression tests to test the research hypotheses. The findings revealed that self-harm behavior was not significantly influenced by mental health literacy (Sig 0.218 > 0.05, t-count 1.234). Help-seeking, on the other hand, was found to significantly influence self-harm behavior (Sig 0.000 0.05, t-count -3.916). R-square's coefficient of determination was 0.046, indicating that mental health literacy and help-seeking together explained 4.6% of the variability in self-harm behaviour. Further research into preventing and treating self-harm is advised, along with a greater emphasis on the value of appropriate and efficient help-seeking among university students.